Heart rate variability, physical activity and daily eustress and distress among Finnish employees - Ritari, Ilmari (2024)
The interaction between heart rate variability (HRV), physical activity (PA) and perceived stress levels has gained research interest in recent years due to its multifaceted implications for occupational health and wellbeing. This study examined the relationship between HRV and perceived stress levels among Finnish employees while also assessing the potential moderating effect of PA on this interplay. The objective was to enhance the empirical understanding of these physiological and psychological constructs, thereby contributing to a more nuanced comprehension of the mechanisms through which HRV and PA may influence, or be influenced by, individuals´ subjective experiences of stress.